Effect of Probiotics on Gastrointestinal Health Through the Aryl Hydrocarbon Receptor Pathway: A Systematic Review - Adrián De la Rosa González; Sol Guerra-Ojeda; María Alejandra Camacho-Villa; Alicia Valls; Eva Alegre; Ronald Quintero-Bernal; Patricia Martorell; Empar Chenoll; Marta Serna-García; Maria D. Mauricio; Eva Serna (Foods)
Probiotics are living microorganisms recognized for conferring health benefits on the host by modulating the gut microbiota. They interact with various signaling pathways, including the aryl hydrocarbon receptor (AhR), which plays a crucial role in maintaining intestinal homeostasis and immune function. The activation of AhR by probiotics has been associated with benefits such as improved intestinal barrier function, reduced inflammation, and modulation of immune responses. This systematic review aims to summarize current knowledge on the signaling of AhR, mediated by probiotics in physiological conditions and gastrointestinal pathologies. We conducted a comprehensive search across databases, including PubMed and Embase, up until July 2024. Out of 163 studies screened, 18 met the inclusion criteria. Our findings revealed in healthy populations that probiotic consumption increases the production of AhR ligands promoting intestinal immune tolerance. Furthermore, in populations with gastrointestinal pathologies, probiotics ameliorated symptoms through AhR activation by Trp metabolites, leading to the upregulation of the anti-inflammatory response.